2018
DOI: 10.3847/1538-4357/aab153
|View full text |Cite
|
Sign up to set email alerts
|

Successive X-class Flares and Coronal Mass Ejections Driven by Shearing Motion and Sunspot Rotation in Active Region NOAA 12673

Abstract: We present a clear case study on the occurrence of two successive X-class flares including a decade-class flare (X9.3) and two coronal mass ejections (CMEs) triggered by shearing motion and sunspot rotation in active region NOAA 12673 on 2017 September 6. A shearing motion between the main sunspots with opposite polarities started on September 5 and even lasted after the second X-class flare on September 6. Moreover, the main sunspot with negative polarity rotated around its umbral center and another main suns… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(89 citation statements)
references
References 93 publications
6
80
1
1
Order By: Relevance
“…Démoulin & Pariat 2009;Palmerio et al 2017). In the particular case under study, images in the extreme ultraviolet SDO/AIA filter at 94 Å (Figure 1(g)-(i)) suggest that AR 12673 was characterised by a negative chirality as indicated by the presence of a reverse-S sigmoid in its northern part, which is also consistent with the recent analyses by Mitra et al (2018), Yan et al (2018) and Price et al (2019). Although cases of inconsistency between the chirality of the source region and that of the erupted CME have been observed (e.g.…”
Section: Chirality and Tilt Of The Flux Ropessupporting
confidence: 89%
“…Démoulin & Pariat 2009;Palmerio et al 2017). In the particular case under study, images in the extreme ultraviolet SDO/AIA filter at 94 Å (Figure 1(g)-(i)) suggest that AR 12673 was characterised by a negative chirality as indicated by the presence of a reverse-S sigmoid in its northern part, which is also consistent with the recent analyses by Mitra et al (2018), Yan et al (2018) and Price et al (2019). Although cases of inconsistency between the chirality of the source region and that of the erupted CME have been observed (e.g.…”
Section: Chirality and Tilt Of The Flux Ropessupporting
confidence: 89%
“…All these observations of flare loops or ribbon motions during "type I" confined flares provide the evidence for slipping magnetic reconnections between different sets of magnetic systems. The constant flux emergence and shearing motion (Figure 1) probably help to accumulate the current at the interface between the two systems (Krall et al 1982;Yan et al 2018). Magnetic reconnections could occur within the current layer in the vicinity of QSLs, similar to the simulations of Aulanier et al (2005).…”
Section: Discussionmentioning
confidence: 70%
“…They had proposed a block-induced complex structure for a flare-productive AR. Similarly, Yan et al (2018) suggested the sunspot rotation and shearing motion played an important role in the buildup of free-energy and the formation of flux ropes in the corona which produces solar flares and CMEs. We believe that the long term evolution of the AR has characteristic clues for the nature and strength of the activity, which by studying different AR cases can help constrain the space-weather prediction models.…”
Section: Summary and Discussionmentioning
confidence: 97%